A three-dimension finite element analysis to evaluate the stress distribution in tooth supported 5-unit intermediate abutment prosthesis with rigid and nonrigid connector - Modi, Ritesh; Kohli, Shivani; Rajeshwari, K.; Bhatia, Shekhar (European Journal of Dentistry, 2015)
Objective: The aim of the study is to evaluate the stress distribution in tooth supported 5-unit fixed partial denture (FPD) having tooth as pier abutment using rigid and nonrigid connectors respectively, under simultaneous and progressive loading. Material and Methods: The three-dimensional (3D) finite element program (ANSYS software) was used to construct the mathematical model. Two 5-unit FPD'S were simulated, one with rigid connector and another one with nonrigid connector. For analysis, each of these models were subjected to axial and oblique forces under progressive loading (180, 180, 120, 120, 80 N force on first and second molars, premolars and canine respectively) and simultaneous loading (100, 100, 100, 100, 100 N force on first and second molars, premolars and canine respectively). Results: The rigid and nonrigid connector design have effect on stress distribution in 5-unit FPDs with pier abutments. Conclusion: Oblique forces produce more stresses than vertical forces. Nonrigid connector resulted in decrease in stress at the level of prosthesis and increase in stress at the level of alveolar crest.
Keywords: Connectors; finite element analysis; pier abutment; stress distribution; tooth supported